Knowledge, attitudes, practices (KAP) and control of rabies among community households and health practitioners at the human-wildlife interface in Limpopo National Park, Massingir District, Mozambique. - Milton Mapatse; Claude Sabeta; José Fafetine; Darrell Abernethy (Public Library of Science (PLoS), 2022)
Background Rabies is a viral zoonotic disease that kills more than 26,000 people each year in Africa. In Mozambique, poverty and inadequate surveillance result in gross underreporting and ineffective control of the disease in animals and people. Little is known of the role of human attitudes and behaviour in prevention or control of rabies, thus this study was undertaken to assess the knowledge, attitudes and practices amongst selected households and health practitioners in one affected area, the Limpopo National Park (LNP), Massingir district. Methodology A cross-sectional study was conducted among 233 households in eight villages in LNP and among 42 health practitioners from eight health facilities in Massingir district between 2016 and 2018. Consenting household representatives aged 18 years or over were purposively selected. A KAP survey was administered to obtain information on dog ownership and knowledge of rabies, host species affected, modes of transmission, symptoms, recommended treatment and preventive methods. Similar to household study participants, health practitioners were purposively selected and completed the questionnaire during the investigators' visit. The questionnaire sought information on knowledge of rabies, management of bite wounds, vaccination sites and schedules of pre- and post-exposure prophylaxis. Descriptive and inferential data analyses were performed using SPSS software version 18.0. Results Approximately twenty per cent (18.9%; 95% CI: 14.3-24.3) and 13.3% (95% CI: 9.4-18.1) of households had good knowledge and practices of rabies, respectively. For health practitioners, only 16.7% (95% CI: 7.5-31.9) had good knowledge, whilst 33.3% (95% CI: 20.0-49.7) adopted adequate attitudes/practices towards the disease. Conclusions/significance In conclusion, both households and health practitioners displayed poor levels of knowledge and adopted bad attitudes and practices towards rabies. The former, had more gaps in their attitudes and practices towards the disease. Village location and education level (P < .05) and similarly, sex and occupation, were found to be statistically associated with good knowledge of rabies among households as compared to HPs. Overall, a lack of community-based education and professional retraining courses contribute significantly to poor awareness of rabies in the LNP of Mozambique. Enhancing public health knowledge should consequently reduce dog-mediated human rabies deaths in this country.